2005
DOI: 10.1111/j.1365-2672.2005.02608.x
|View full text |Cite
|
Sign up to set email alerts
|

Community survey of ammonia-oxidizing bacteria in full-scale activated sludge processes with different solids retention time

Abstract: Aims: To study the effects of different solids retention time (SRT) on the nitrification activity and community composition of ammonia-oxidizing bacteria (AOB) in two full-scale activated sludge processes during a 5-month period. Methods and Results: The AOB community composition was analysed using fluorescence in situ hybridization (FISH) and denaturing gradient gel electrophoresis (DGGE), and the identified populations were enumerated by quantitative FISH. Potential nitrification rates were determined in bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 40 publications
7
34
0
Order By: Relevance
“…Thus, the AOB cells in the 2-day system (with higher amoA mRNA levels) could quickly propagate under short SRT operation, thereby reducing the possible cellular washout and ultimately system failure. These observations are well supported by previous reports that indicate decreased SRT results in an increased substrate loading and oxidation rate when normalized per unit of activated sludge [10,20].…”
Section: Resultssupporting
confidence: 92%
“…Thus, the AOB cells in the 2-day system (with higher amoA mRNA levels) could quickly propagate under short SRT operation, thereby reducing the possible cellular washout and ultimately system failure. These observations are well supported by previous reports that indicate decreased SRT results in an increased substrate loading and oxidation rate when normalized per unit of activated sludge [10,20].…”
Section: Resultssupporting
confidence: 92%
“…and not to Nitrosospira spp. This result is consistent with most previous studies [2,[22][23][24][25][26][27][28][29][30] but is in contrast to a few studies that found Nitrosospira spp. to be the dominant AOB [27,31].…”
Section: Phylogenetic Analysissupporting
confidence: 93%
“…AOB belonging to this cluster are often recovered from freshwater, sediments, soils, wastewater treatment plants, and other environments [22,24,25,32,33]. A study of isolates of the N. oligotropha cluster revealed that they have very low K s values for free ammonia, ranging from 0.027 to 0.059 mg$L -1 [34].…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The size and morphology of the investigated AOB populations are consistent with those reported in the literature [38,39], although AOB clusters can also be present in larger aggregates depending on the sample age [39,40].…”
Section: Fish and Microscopy Image Analysessupporting
confidence: 89%